ANALISIS PENGARUH LINGKUNGAN KERJA ,DISIPLIN KERJA DAN FASILITAS KERJA TERHADAP KINERJA PEGAWAI ASN DI DINAS PERINDUSTRIAN, PERDAGANGAN, ENERGI, DAN SUMBER DAYA MINERAL PROVINSI SUMATERA UTARA - Pane, Khairunnisa Annabila; Anwar, Yohny; Wahyono, Teguh (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2025)
The results of this research aim to understand and analyze the influence of the work environment, work discipline and work facilities on the performance of ASN employees of the Department of Industry, Trade, Energy and Mineral Resources of North Sumatra Province. This research uses a quantitative approach. The sample in the study was 72 ASN employees using random sampling technique. The results of this research show that the work environment partially has a positive and significant effect on employee performance with a t valuecount 4,839 > ttable 1.995 and a significant value of 0.00 <0.05. Work Discipline partially has a positive and significant effect on employee performance with the t valuecount 5,998 > ttable 1.995 and a significant value of 0.00 <0.05. Work Facilities do not have a positive and significant effect on employee performance with a t valuecount 0,045 < ttable 1.995 and a significant value of 0.964 > 0.05. Work Environment, Work Discipline and Work Facilities simultaneously have an influence on the Performance of ASN Employees of the Department of Industry, Trade, Energy and Mineral Resources of North Sumatra Province, F valuecount 103.893 > Ftable 2.73 and a significant value of 0.00 <0.05.